Factors Affecting X-ray Radiation Safety Measures in the Radiology Unit of Putri Hijau Hospital, Medan - Ferusgel, Agnes (Fakultas Ilmu Kesehatan, Universitas Borneo Tarakan, 2018)
The problems examined in this study are about the safety measures of x-ray radiation in the radiology unit of Putri Hijau Hospital, Medan. This study aims to determine the factors that influence the safety measures of workers in the radiology unit of Putri Hijau Hospital, Medan. This type of research uses a cross sectional study. The population in this study were all workers in the radiology unit of Putri Hijau Medan Hospital, which numbered 30 people as radiology workers. The study sample used a total population of 30 people. Data analysis uses multiple logistic regression analysis. The results showed that there was an influence of sex (p = 0.032), knowledge (p = 0.049) and work attitude (0.019) on occupational health and safety measures of workers in the Radiology Unit of Putri Hijau Hospital Medan. It is recommended to research sites to routinely make training on X-ray radiation safety work and monitor workers, especially radiology units, to always act according to the rules of occupational safety and health.Â Keywords: Knowledge, Attitudes, Workers, X-Ray Radiation Safety Measures